Interpreting change: International challenges and variations in foreign policy beliefs as explanations for shifts in China's policy towards the European Union. (September 2015) - Gaenssmantel, Frank
This article examines why and how China upgraded its engagement with the European Union (EU) in the years between 2001 and 2004, with reference to pre-existing foreign policy traditions and practices in reform-era China. It argues that most of the observed changes can be explained with reference to two dynamics. First, the changing international environment, mostly with regard to the roles of the United States and the EU, challenged the established approach to foreign policy inherited from Deng Xiaoping, China's pre-eminent leadership figure from the late 1970s to the mid-1990s. In this sense, the shift towards the EU was part of wider efforts to solve this dilemma. Second, differences in how various groups in the Chinese foreign policy establishment understood and implemented Deng's guidelines and their respective influence in policy-making can help to grasp some of the more specific developments in Chinese policy towards the EU in the early 2000s. To supplement this main claim, the article also critically evaluates the changes less well explained by these two dynamics and proposes additional explanations.